PROSES PEWARISAN MAKNA TRADISI TARI REJANG AYUNAN DI DESA PUPUAN, TABANAN, BALI - Sri Lestari, Ni Putu Indah; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
Meaning is a substance in communication that must be obtained from the communication process carried out. The purpose of this study is to see and explain the communication process of the people of Pupuan Village, Tabanan in passing down the meaning of the Rejang Ayunan Dance tradition. This research is a descriptive qualitative research and uses the theory of Harold Lasswell's communication model and the concept of cultural inheritance according to McQuail. The results of this study indicate that the way people pass on the meaning of this tradition includes the process of understanding the meaning of tradition which takes place in three parts, namely family, yowana and society and has gone through three stages of inheritance, namely Internalization, Socialization and Enculturation. Therefore, the people in Pupuan Village, Tabanan, Bali are still preserve the tradition of the Rejang Swing Dance.   Keywords: Rejang Ayunan Dance, inheritance of meaning, communication process